Mandibular canine with two roots - Laura Ricardina Ramírez-Sotelo; Frederico Sampaio Neves; Gina Delia Roque-Torres; Deborah Queiroz de Freitas; Solange Maria de Almeida; Frab Norberto Bóscolo (Editorial Ciencias Médicas, 2013)
The mandibular canine is a robust and long tooth which allows an adequate implantation in the dental arch. It is considered a valuable pillar in many rehabilitating treatments. In order to maintain this important dental element, it is necessary to make a correct diagnosis, for which the knowledge of the different anatomic variations should be kept in mind. The objective of this article is to present a case of a mandibular canine with two roots with their respective root canals. A 21-year-old female patient went to the Radiology Clinic at the Faculty of Odontology of Piracicaba with the indication of a panoramic radiography for preoperative third molars surgery. An unusual root configuration of the mandibular canines was observed. In the cone beam CT, it was observed that the right mandibular canine presented two separate roots, each one with their respective radicular canals. It was concluded that, despite of the low prevalence of anatomical variations, these can occur in the root system of the mandibular canines, as presented in this case report. Key words: mandibular canine, two roots, Cone beam CT.